2021
DOI: 10.3390/jof7070577
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution, Antifungal Susceptibility, and Molecular Epidemiology of Candida Species Causing Candidemia in a Tertiary Care Hospital in Bangkok, Thailand

Abstract: Candida species represent a common cause of bloodstream infection (BSI). Given the emergence of non-albicans Candida (NAC) associated with treatment failure, investigations into the species distribution, fungal susceptibility profile, and molecular epidemiology of pathogens are necessary to optimize the treatment of candidemia and explore the transmission of drug resistance for control management. This study evaluated the prevalence, antifungal susceptibility, and molecular characteristics of Candida species c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
2
23
1
Order By: Relevance
“…With few exceptions, our results show that 26 isolates were cross-resistant to three azole antifungals, and the strains with fluconazole resistance were usually cross-resistant to other azole antifungals, such as itraconazole and voriconazole. These results agree with those obtained by Song et al (2020) and Boonsilp et al (2021) . Conversely, fluconazole resistance was found in 30 of the 133 C. glabrata isolates examined in our present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With few exceptions, our results show that 26 isolates were cross-resistant to three azole antifungals, and the strains with fluconazole resistance were usually cross-resistant to other azole antifungals, such as itraconazole and voriconazole. These results agree with those obtained by Song et al (2020) and Boonsilp et al (2021) . Conversely, fluconazole resistance was found in 30 of the 133 C. glabrata isolates examined in our present study.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, several studies performed in Japan, South Korea, and China also indicated that ST7 is the major genotype associated with C. glabrata ( Dodgson et al, 2003 ; Hou et al, 2017 ; Byun et al, 2018 ; Canela et al, 2021 ). Conversely, Boonsilp et al (2021) have shown that the most common ST is ST55 (60%), followed by ST7 (20%), ST195 (10%), and ST199 (10%), among C. glabrata isolated from blood samples in Bangkok, Thailand. This genetic variation may stem from geographical bias, suggesting that the genetic variation among clinical isolates in a specific area cannot be extended to other areas.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Species distribution and antifungal susceptibility shows considerable geographical variation between individual countries, but trends can generally be elucidated at the continental level, such as the Americas and Europe (Figure 3). Across some continents (Asia, Africa and Oceania), few distinctive trends are observed and are not well-defined due to limited and contrasting data from mostly single-institution studies [103][104][105][106][107][108]. As a result, data from Asia will be assessed briefly and Africa and Oceania will be excluded from this review.…”
Section: Geographical Trendsmentioning
confidence: 99%
“…Across the Asian continent, few distinctive trends in current species distribution and antifungal susceptibility can be concluded due to limited, contrasting data from mostly single-institution retrospective surveillance studies. Generally, C. tropicalis might be the primary etiologic agent of IC across west Asia (e.g., Pakistan, India) whilst in east Asia (e.g., China), C. albicans remains the most prevalent species with widely varied contributions from NAC species [103][104][105][106][107][108]. This is unsurprising given that China covers a land area of 9.38 million km 2 and has a population of nearly 1.5 billion, which will inevitably show regional variations in pre-disposing population dynamics and risk factors that influence species distribution.…”
Section: Asiamentioning
confidence: 99%